Applicability of precision weed detection technologies - Riczu, Péter; Tamás, János (Acta Agraria Debreceniensis, 2013)
In an agricultural field or horticultural plantation, weeds compete with cultivated plants for water and nutrients. The transpirated water by the weeds is needed to be replaced, which saddles surplus costs on the farmer, which could reduce the profitability of crop production. The aim of the precision plant protection system is to protect cultivated plants by applying site-specific technologies and optimized herbicides combination and methods, without environmental damage. The first step of precision weed control is the scouting for weeds. Traditional and modern (passive and active remote sensing) weed surveying technologies are available to detect weeds. The examination was carried out in an intensive apple orchard with drip irrigation system, protected by hail net of the Study and Regional Research Farm of the University of Debrecen near Pallag. The spectral-based weed detection was worked out by the Tetracam ADC broadband multispectral camera and the GreenSeeker 505 vegetation indexmeter. A strong correlation observed between vegetation indices and weed coverage. Based on the collected data, weed maps are created in appropriate software environment, thus the spatial distributions of the weeds are determined. The species level discrimination and the recognition of weed structural parameters were executed based on the 3D point cloud data by Leica ScanStation C10 laser scanner.